Liberia : 2011 Sixth Review Under the Three-Year Arrangement Under the Extended Credit Facility, Request for Extension of the Arrangement, and Augmentation of Access; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, the staff report for the review under the three-year arrangement under the Extended Credit Facility is discussed. Investment in iron ore and commercial agriculture and rebound in rubber prices are important for growth. Fiscal, monetary, and financial policies are discussed. An update of external debt sustainability confirms the low risk of debt distress rating. IMF staff supports the new indicative floor on education and health spending in FY2012, and the performance criterion on the Central Bank of Liberia (CBL) payment are discontinued.